Role of nitric oxide in eicosanoid synthesis and uterine motility in estrogen-treated rat uteri. - Franchi, A M (1994)
Cholinergic stimulation of vascular endothelin activates NO synthase (NOS), leading to generation of NO from arginine. This NO diffuses to the overlying vascular smooth muscle and causes vasodilatation. NOS has also been found in the central and peripheral nervous systems and it is clear now that NO plays an important role as a neurotransmitter. Here we investigate the role of NO in controlling contraction of uterine smooth muscle. Our previous work showed that NO activates the cyclooxygenase enzyme in the hypothalamus, leading to production of prostaglandin E2 (PGE2). We began by determining whether NO was involved in production of arachidonic acid metabolites in the uterus. Uteri were removed from female rats that had been treated with estrogen (17 beta-estradiol). Control animals were similarly injected with diluent. Tissues were incubated in vitro in the presence of [14C]arachidonic acid for 60 min. Synthesis of PGs and thromboxane B2 (TXB2) was markedly stimulated by sodium nitroprusside (NP), the releaser of NO. The effect was greatest on TXB2; there were no significant differences in increases of different PGs. The response to NP was completely prevented by Hb, a scavenger of NO. The inhibitor of NOS, NG-monomethyl-L-arginine (NMMA), significantly decreased synthesis of PGE2 but not the other prostanoids (6-keto-PGF1 alpha and PGF2 alpha). Addition of Hb to scavenge the spontaneously released NO inhibited synthesis of 6-keto-PGF1 alpha, PGE2, and PGF2 alpha, but not TXB2. There was a much lesser effect on products of lipoxygenase, such that only 5-hydroxy-5,8,11,14-eicosatetraenoic acid (5-HETE) synthesis was increased by NP, an effect that was blocked by Hb; there was no effect of NMMA or Hb on basal production of 5-HETE. Thus, NO stimulates release of the various prostanoids and 5-HETE; blockade of NOS blocked only PGE2 release, whereas Hb to scavenge the NO released also blocked synthesis of 6-keto-PFG1 alpha, PGE2, and PGF2 alpha, indicating that basal NO release is involved in synthesis of all these PGs, especially PGE2. Presumably, NMMA did not block NOS completely, whereas Hb completely removed released NO. This may explain the different responses of the various prostanoids to NMMA and Hb. To determine the role of these prostanoids and NO in control of spontaneous in vitro uterine contractility in the estrogen-treated uterus, the effect of blocking NOS with NMMA and of scavenging NO produced by Hb on the time course of spontaneous uterine contractility was studied. Surprisingly, blockade of NOS or removal of NO by Hb prevented the spontaneous decline in uterine motility that occurs over 40 min of incubation. We interpret this to mean that NO was released in the preparation and activated guanylate cyclase in the smooth muscle, resulting in production of cGMP, which reduces motility and induces relaxation. When the motility had declined to minimal levels, the effect of increased NO provided by NP was evaluated; apparently by stimulating the release of prostanoids, a rapid increase in motility that persisted for 10 min was produced. This effect was completely blocked by Hb. The action of NO was also blocked by indomethacin, indicating that it was acting via release of PGs. Apparently, when motility is low, activation of PG synthesis by NO to activate the cyclooxygenase enzyme causes a rapid induction of contraction, whereas, when motility is declining, NO acts primarily via guanylate cyclase to activate cGMP release; the action of the prostanoids released at this time is in some manner blocked.